2019
DOI: 10.3346/jkms.2019.34.e279
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Waning Immunity at 6 Months after Both Trivalent and Quadrivalent Influenza Vaccination in Korean Children Aged 6–35 Months

Abstract: Background: The titer of influenza vaccine-induced antibodies declines over time, and younger children have lower immunogenicity and shorter duration of immunity. This study aimed to compare persistence of antibody at 6 months after influenza vaccination according to influenza virus strains, vaccine type, antigen dose, and primed status in children aged 6 to 35 months. Methods: A total 124 healthy children aged 6 to 35 months were enrolled from September to December 2016 at 10 hospitals in Korea and randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…On the other hand, the decrease in antibody titers after vaccination is common for different vaccines. Some authors have reported a more significant decrease in antibodies against influenza B strains than A strains after six months of vaccination ( 28 ). Others have reported that antibody levels and avidity decrease between 8% and 23% after six months to 20 years of vaccination against measles, mumps, and rubella ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the decrease in antibody titers after vaccination is common for different vaccines. Some authors have reported a more significant decrease in antibodies against influenza B strains than A strains after six months of vaccination ( 28 ). Others have reported that antibody levels and avidity decrease between 8% and 23% after six months to 20 years of vaccination against measles, mumps, and rubella ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is more complicated for children under 9 years of age who start their influenza vaccination for the first time, because they are even more vulnerable to the infection and need two shots over an at least 4 week interval 3. The article by Lee et al4 in this issue provides valuable evidence to relieve the concerns on the timing of vaccination against influenza A strains. The authors prospectively evaluated the persistence of immunity against influenza strains at 6 months after vaccination in young children and it was favorable against the influenza A strains.…”
mentioning
confidence: 99%